Comparative Evaluation of Stress at the Implant Bone Interface Between Short Implants and Long Implants Using BioHPP Abutment- An In vitro Study - C Thamarai; Annapoorni Hariharan; K Thanya; Aaron G. Baby; A R Saishree; B. Devi Parameswari; D Narmadha (Journal of Pharmacy and Bioallied Sciences, 2025)
Aim: To compare and evaluate the stress at the implant–bone interface between short implants and long implants using BioHPP abutment. Settings and Design: In vitro study. Materials and Methodology: 10 PMMA mandibular models with implants, used in the study, were divided into 2 groups, Group L—10 implants (diameter—4.5 mm; length—14 mm); Group S—10 implants (diameter—5 mm, and length—5.2 mm). BioHPP abutments were fixed over the implant fixtures in both the groups, and monolith crowns were cemented. The crowns were then loaded with an universal testing machine, and the resultant stress was recorded using a strainmeter. A comparative study is done between Groups L and S to evaluate the stress distribution at the implant–bone interface. Statistical Analysis Used: Descriptive statistics (mean and standard deviation) were used to analyze stress in both Group L and Group S. Normality was checked with the Shapiro–Wilk test, and variance equality was assessed using Levene’s test. Intergroup comparisons were made using an unpaired t test, with a P value < 0.05 considered statistically significant. Results: The stresses at the implant–bone interface between the Group L and Group S are statistically insignificant for all type of load application at various points of loading. Conclusion: Based on the results, it can be concluded that the use of long or short implants with BioHPP abutments and monolith crowns will not affect the stresses at the implant–bone interface.